Treatment of chronic heart failure with β adrenergic blockade beyond controlled clinical trials: the BRING-UP experience. (1st March 2003) - Maggioni, A P; Sinagra, G; Opasich, C; Geraci, E; Gorini, M; Gronda, E; Lucci, D; Tognoni, G; Balli, E; Tavazzi, L
Abstract : Background: Several large controlled trials have shown that β blockers given to patients with heart failure (New York Heart Association functional class II–IV) reduce morbidity and mortality. Despite these impressive results, implementing the use of β blockade in clinical practice appears slow and difficult. The BRING-UP study was designed to tackle this problem. Objectives: To accelerate the adoption of β blockade in clinical practice; to provide an epidemiological estimate of the proportion of patients with heart failure suitable for this treatment in general cardiology care; and to assess effectiveness of these drugs outside the setting of clinical trials. Methods: The design of the study and recommendations derived from available evidence on the use of β blockers were discussed with cardiologists during regional meetings. All consecutive heart failure patients in a one month period, whether treated or not with β blockers, were eligible for the study. In each patient, the decision to prescribe a β blocker was a free choice for the participating physicians. All centres were provided with carvedilol, metoprolol, and bisoprolol at appropriate doses; the choice of the drug and dosage was left to the responsible clinician. All patients were followed for one year. Results: 197 cardiological centres enrolled 3091 patients, 24.9% of whom were already on β blocker treatment at baseline. β Blockers were newly prescribed in 32.7% of cases, more often in younger and less severely ill patients. The mean daily dose of the drugs used at one year corresponded to about 70% of the maximum dose used in clinical trials. Starting treatment with β blockers did not affect the prescription or dosage of other recommended drugs. The overall rate of β blocker treatment increased over the year of the study from 24.9% to 49.7%. During the 12 month period, 351 deaths occurred (11.8%). In multivariate analysis, the use of β blockers was independently associated with a better prognosis, with a relative risk of 0.60 and a lower incidence of hospital admissions for worsening heart failure. Conclusions: The implementation of β blockers in clinical practice is feasible and could be accelerated. These drugs are associated with a lower mortality and reduced hospital admission rates, not only in clinical trials but also in the normal clinical setting.